PENGEMBANGAN SISTEM BERBASIS WEB MARKETPLACE PAKAN TERNAK DAN PRODUK PETERNAKAN (EPAKAN) MENGGUNAKAN FRAMEWORK LARAVEL - Ahmad Paruhum; Astria Hijriani; Ardiansyah Ardiansyah (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Efforts to develop livestock production that bear a stable and quality feed load, because feed is a determining factor for business continuity and continuity. The creation of the android-based ePakan application makes it very easy for breeders and non-breeders to buy and sell livestock products, because access is via smartphones. A good marketplace application and needs continuous updates to the appropriate application based on the needs of the user (end user). The web-based ePakan application is expected to make it easier for users to access the ePakan marketplace. The development of the web-based ePakan marketplace system was built using the PHP programming language with the laravel framework. The method used for system development uses Extreme Programming. The features available in this web-based ePakan marketplace include purchasing products, adding products, adding baskets, requesting partners, canceling orders, requesting to withdraw balances. From the results of Blackbox testing with the Equivalence Partitioning method, the web-based ePakan Marketplace functions as needed.